PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2011 – 2014) - Mhd. Hidayat; Restu Agusti; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to look at the effect of Good Corporate Governance characteristics and the size of the company's to earnings management. This study population is LQ45 companies listed in Indonesia Stock Exchange 2011-2014 period. Based on the purposive sampling method, acquired 22 companies as samples in this study. Research data analysis techniques using Multiple Linear Regression Analysis with SPSS statistical program. The results of study carried out showed that the presence of independent board, institutional ownership, the size of the company's audit committee and significant effect on earnings management. While the managerial ownership no significant effect on earnings management. The coefficient of determination (R2) of 0.439, or 43.9%, meaning that earnings management is explained by the presence of independent board, institutional ownership, the audit committee and the size of the company amounted to 43.9%. While 56.1% is explained by other variables that are not included in this study.Keywords: Earnings management, good corporate governance and the Company Size